Ethyl Acetate Fraction of Chestnut Honey Attenuates Scopolamine-Induced Cognitive Impairment in Mice and Glutamate-Induced Neurotoxicity in HT22 Cells - Yun Hee Jeong; Wei Li; Hye Jin Yang; Se-Gun Kim; Hong Min Choi; Jang-Gi Choi; You-Chang Oh (MDPI AG, 2024)
Chestnut honey has various benefits, such as antioxidative, anti-inflammatory, immunomodulatory, antibacterial, and antiviral effects. However, the effects of chestnut honey or the ethyl acetate fraction of chestnut honey (EACH) on neurodegenerative diseases and their related cognitive impairment and neurotoxicity have not yet been established. Therefore, in this study, we investigated the mitigating effect of the EACH on scopolamine (SCO)-injected cognitive decline in mice and glutamate-exposed neurotoxicity in HT22 cells. EACH administration significantly reversed SCO-induced cognitive decline in mice, as demonstrated through the Morris water maze and passive avoidance tests. The EACH treatment showed a significant alleviation effect by recovering more than 80% of the cell viability decrease induced by glutamate exposure in the HT22 neuronal cell model. Furthermore, the EACH significantly reduced reactive oxygen species accumulation, lactate dehydrogenase release, mitochondrial depolarization, and neuronal apoptosis. The EACH regulated the level of apoptosis-related proteins, induced the nuclear translocation of nuclear factor-E2-related factor 2 (Nrf-2) and the expression of related antioxidant proteins, and induced the phosphorylation of tropomyosin-related kinase receptor B (TrkB)/cAMP-calcium response element-binding protein (CREB) and the expression of brain-derived neurotrophic factor. These data indicate that the EACH can prevent neurons from oxidative damage and improve cognitive dysfunction by activating Nrf-2 and TrkB/CREB signaling pathways. Therefore, the EACH demonstrates potential therapeutic value in mitigating oxidative stress-induced neurotoxicity, cognitive decline, and related neurodegenerative diseases.